Effect of prolonged wakefulness on electroencephalographic oscillatory activity during sleep. (26th December 2013) - Olbrich, Eckehard; Landolt, Hans Peter; Achermann, Peter
Summary The human sleep electroencephalogram (EEG) is characterized by the occurrence of distinct oscillatory events such as delta waves, sleep spindles and alpha activity. We applied a previously proposed algorithm for the detection of such events and investigated their incidence and frequency in baseline and recovery sleep after 40 h of sustained wakefulness in 27 healthy young subjects. The changes in oscillatory events induced by sleep deprivation were compared to the corresponding spectral changes. Both approaches revealed, on average, an increase in low frequency activity and a decrease in spindle activity after sleep deprivation. However, the increase of oscillatory events in the delta range and decrease in the sigma range occurred in a more restricted frequency range compared to spectral changes. The mean relative power spectra showed a significant increase in theta and alpha activity after sleep deprivation while, on average, the event analysis showed only a weak effect in the theta band. The reason for this discrepancy is that the spectral analysis does not distinguish between diffuse activity and clearly visible temporally localized oscillations, while the event analysis would detect only the latter. Additionally, only a few individuals clearly showed activity in the theta or alpha frequency bands. Conversely, event analysis revealed that some individuals showed an increased rate of sleep spindles after sleep deprivation, a fact that was not evident in the relative power spectra due to a decrease in background activity. The two methods complement each other and facilitate the interpretation of distinct changes induced by prolonged wakefulness in sleep EEG.